Sanción, reposición e indemnización como cons ecuencias autónomas de la infracción administrativa: una lectura a partir del artículo 232.1 de la Ley del Procedimiento Administrativo General - Tírado Barrera, José Antonio (Revista de Derecho, 2019)
The following essay analyzes the relationship between the consequences of an administrative offense, in other words, penalty, corrective measure (or remedial) and compensation, as governed by the Administrative Procedure Law General (LPAG-Ley del Procedimiento Administrativo General). With this purpose, Article 232.1 of the LPAG is studied as a general rule governing these relationships and also diverse sectoral legislation is analyzed in order to appreciate the way the legal system has regulated these situations in diverse specific situations. It is clear that at policy level there is a clear conceptual autonomy between these figures even though it is still insufficient to determine all its implications in order to avoid interpretative errors that may limit its scope.